Impact of Melt Refining on Secondary Al-Si Alloys’ Microstructure and Tensile Mechanical Performance - Wei Gu; Huixin Jin; Xue Wang; Jiajun Jiang (Metals)
Secondary Al-Si alloys typically encompass several impurities that substantially influence the materials’ microstructure and mechanical performance. This study employed a composite addition of chlorinated salt fluxing and an aluminum–boron master alloy to reduce the levels of the impurity elements magnesium (Mg), titanium (Ti), and vanadium (V) in secondary Al-Si alloys. The investigation of the performance mechanism revealed that the distribution of alloys’ grain orientation and the ratio of small-angle grain boundaries were modified via synergistic purification, leading to the refined microstructure and mechanical performance of secondary Al-Si alloys. The removal rates of impurity elements under these optimal refining conditions were 89.9% for Mg, 68.9% for Ti, and 61.5% for V. The refined alloy exhibited a 45.5% decrease in grain size and a 28.7% improvement in tensile strength compared to the raw material. These findings demonstrate that fluxing can improve the extraction of Ti and V from secondary Al-Si alloy melts of aluminum–boron master alloys, providing a new cost-effective strategy for the removal of impurities and the optimization of the properties of secondary Al-Si alloys.